The Relationship between Physical Environmental Sanitation and the Incidence of Acute Respiratory Infections (ARI) in Toddlers in the Lepo-Lepo Health Center Working Area, Kendari City - Ismawati, Ismawati; Azizi Jayadipraja, Erwin; Adi Surya, Ridwan (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction : Acute Respiratory Infections are very big impact if it is not treated, especially if it attacks children. Besides being able to interfere with the child's growth and development, it can also cause death. The prevalence of ARI in 2020 was 28.3%, in 2021 it decreased to 25.3%, and in 2022 it increased again to 29.65% and in 2023 it increased to 30.8%. The aim of the research is to determine the relationship between sanitation of the physical environment in the home with the incidence of Acute Respiratory Tract Infections (ARI) in children under five in the Lepo-Lepo Health Center, Kendari City. Method : This type of research is quantitative research with a Cross Sectional Study design. The population is all 2,998 children under five at the Lepo-Lepo Health Center in 2023 and the sample is 71 children under five taken using the accidental sampling technique. Sample identity data were obtained using a questionnaire. Data on ventilation area, temperature, humidity, lighting and dust particles are carried out by observation. Result : The Chi-Square test results obtained a p value of 0.000, φ = 0.636 (ventilation area), a p value of 0.000, φ =0.611 (temperature), a p value of 0.000 and φ = 0.58 (humidity). p value 0.000, φ =0.579 (lighting),, p value 0.000 and φ =0.731 (dust particles). Conclusion: The relationship between the area of air ventilation, temperature, humidity, lighting, dust particles, with the incidence of ARI in toddlers.